ANALISIS MANAJEMEN OPERASIONAL PADA PT SINDO MANUFAKTUR INDUSTRI - Fiona; Theophilia, Jocelyn; Juniarty, Shely; Ardiyano, Benwanto; Hutagaol, Sherina Romaito Br; Cuandra, Fendy (Transpublika Publisher, 2023)
The current business environment has prompted various companies to develop strategies to stay competitive. One effective way to do this is through good operational management. PT Sindo Manufaktur Industri is a manufacturing company that specializes in mass production and contract manufacturing services for various industrial products. The company has recognized the importance of operational management and has taken steps to improve it. The objective of this research is to analyze the operational management of PT Sindo Manufaktur Industri. This study uses primary qualitative data and collects information through interviews with the company's operational manager. The research findings reveal that PT Sindo Manufaktur Industri has not implemented many good operational strategies at present, but this is not necessary as their business processes are not complex. As their business expands in the future, they can consider implementing various operational management strategies suggested by the authors of this study.